Spectroscopic Determinants in the Reaction Center of Rhodopseudomonas Viridis - Eccles, Joseph (1988)
Assignments are proposed for the long wavelength absorption bands observed in the reaction center of Rhodopseudomonas viridis. The assignments are based on a theoretical treatment in which quantum mechanical calculations are first carried out on the individual chromophores of the reaction center. The energies and wave functions that are obtained are then introduced into an exciton-type perturbation treatment in which extensive configuration interaction is carried out between the excited states of the four bacteriochlorophylls and two bacteriopheophytins of the reaction center. Calculated values for absorption maxima, transition moments, linear dichroism, and rotational strength are compared with experiments in an attempt to distinguish among different assignments. The calculations alone do not lead to unambiguous assignments; indeed it is difficult to account for the reaction center spectra without introducing assumptions as to the effects of the protein on the energy levels of the individual molecules. Even if these effects are treated as free parameters, the experimental spectra still provide useful constraints that restrict the models that are possible. The major result of this work is that the weak 850-nm absorption band is due, primarily, to the higher energy exciton state of the bacteriochlorophyll special pair. Accounting for the 960-nm absorption band of the low energy exciton state of the special pair requires either that a large spectroscopic effect of the protein be introduced, or possibly, that charge transfer states play a major spectroscopic role. The difference in spectra seen in the formation of oxidized or triplet state reaction centers can be understood in terms of a combination of electrochromic effects and modified exciton interactions.